MASALAH PENGENAAN IURAN PENGELOLAAN LINGKUNGAN DI APARTEMEN MANGGA DUA COURT: The Problem Of Imposing Environmental Management Fees At Mangga Dua Court Apartment - Zifanya Kesysha Ramadhani; Anda Setiawati (Faculty of Law, Universitas Trisakti, 2024)
Living in apartment will burdened with obligation to pay Environmental Management Fees. In several cases, developers who previously PPPSRS administrators are unwilling to pay fees if their management has transferred to new administrators from apartment owners. Consequently, issue of fees withdrawal leads to disputes in court. The problem in this research is what the basis for the imposition of fees at the Mangga Dua Court Apartment and whether the judge's consideration in decision No. 190/Pdt.g/2021/PN Jkt.Utr which ordered PT Duta Pertiwi to pay fees is in line with the provisions of the law. Research method uses a type of normative legal research by using secondary data obtained trough library research by descriptive research. The results of the research by the judges of the North Jakarta District Court in decision number 190/Pdt.G/2021/PN Jkt. Utr stated that PT. Duta Pertiwi's actions were acts default for violating the bylaws of the Mangga Dua Court Apartment and the authority to withdraw fees in PPPSRS management or Management Board appointed by the PPPSRS based on PPSRS bylaws. Conclusion, avoiding similar things, it is better for apartment owners and residents to carry out their obligations and fulfill the provisions in the PPPSRS by laws.